ATMOSFER KEBEBASAN PERS (ANTARA HUKUM, ETIKA, DAN PROFESIONALISME WARTAWAN) - Abdul Halik (Fakultas Dakwah dan Komunikasi, 2020)
Journalism is a profession that provides information services to the public. The duty and obligation of journalists are to convey and pass on information or truth to the public. Some things that journalists need to pay attention to in carrying out their duties are: not arrogant, honest, towards the truth, prioritizing accuracy and acting quickly. Journalists have a journalistic code of ethics that must be obeyed and upheld. The code of ethics contains the ethical boundaries of journalists in carrying out their profession which includes among others: responsibility, freedom, independence, truth, impartiality, fairness and fairness.